Pengaruh Perencanaan, Pelaksanaan dan Penilaian Kerja Manajemen Puskesmas Terhadap Kualitas Pelayanan di UPT Puskesmas Sibolangit Tahun 2024 - Elvipson Sinaga; Marta Imelda Br Sianturi (STIKES Columbia Asia Medan, 2024)
The quality of service at UPT Puskesmas Sibolangit is still not good. The quality of service at UPT Puskesmas Sibolangit is still not good which is related to the management of the health center which has not been able to carry out its functions properly including: planning, implementation and performance assessment. This study aims to determine the effect of planning, implementation and assessment of health center management work on service quality at UPT Puskesmas Sibolangit. This type of research is an analytical survey study with a cross-sectional design. The population of the study was all employees at the Sibolangit Health Center UPT as many as 52 people and using total sampling. The data collected were primary data and secondary data, primary data were obtained using a questionnaire. The data were analyzed using Multiple Logistic Regression statistical tests with a confidence level of 95%. The results showed that the majority of planning was less than good as many as 28 people (53.8%), the majority of implementation was less than good as many as 28 people (53.8%), the majority of assessment was less than good as many as 29 people (55.8%) and the majority of service quality was less than good as many as 29 people (55.8%). The conclusion of this study is that planning obtained p-value = 0.037 <α=0.05, implementation obtained p-value = 0.037 <α=0.05 and assessment obtained p-value = 0.022 <α=0.05 means that there is an influence of planning, implementation and assessment on the quality of service at the Sibolangit Health Center UPT and the most dominant health center management influencing the quality of service at the Sibolangit Health Center is the assessment variable that has an influence with a strength of influence of 29,153 times. It is recommended to the Head of the Health Center to increase the joint commitment of the leadership and employees and the Head of the Health Center to improve coordination, communication and cooperation by involving all program managers in the management process and for the Health Office to further improve technical guidance to the Health Center on health center management.